Deterministic Modeling of Annual Runoff and Sediment Production Rate for Small Watersheds of Chambal Catchment - Singh, P K; Kumar, Virendra; Purohit, R C (Journal of Agricultural Engineering, 2007)
Deterministic geomorphic modelling is basically a tool for prediction of hydrologic behavior of a basin. Proper scientific planning and management require detailed data to make reliable predictions. In this paper multivariate statistical techniques have been applied to develop dimensionally homogeneous and statistically optimal models for prediction of annual runoff and sediment production rate from the small watersheds of Chambal catchment. The dimensionless geomorphic and rainfall parameters have been used as independent variable in the analysis. The significant components and parameters have been obtained by applying principal component analysis. The validation of the models has also been done. The developed models can be conveniently used to predict the runoff and SPR ofsmall ungauged watershed of Chambal catchment and also other region having similar physiographic characteristics.